Drivers and consequences of business-reference-content (BRC): The role of narrative transportation in B2B communication - Chang Mo Jung (Journal of Business Economics and Management (JBEM), 2021)
COVID-19 is bringing changes in B2B sales and marketing strategies. Digital interaction with potential customers has become more critical. Business-reference content (BRC) is the most shared content, mainly using narrative format, available to potential customers through digital touchpoints. Reducing perceived purchasing risk has been recognized as the primary benefit of using BRC, but empirical research on this has been insufficient. Therefore, this research investigated the underlying mechanisms of BRC and related processes that lower risk perception based on narrative transportation theory. For empirical analysis, a serial-parallel mediating model was established in which BRC type (narrative versus non-narrative) influences purchase intention through the mediation of narrative transportation and perceived purchase risks - functional risk and financial risk. In this experimental study, an online survey was conducted in which 233 purchasing managers in Korean companies participated. The analysis confirmed that the BRC type had a significant effect on the level of receivers' narrative transportation. In addition, serial-parallel mediating effects through narrative transportation (primary mediator) and perceived functional risk and perceived financial risk (secondary mediators) were all significant. This research provides meaningful implications in that it broadens the theoretical understanding of BRC by presenting the integrated BRC effect model. Also, it clarifies the importance of narrative BRC in B2B marketing practices.
Keywords: M41; C83; L20; 650; B2B content marketing; business-reference content; B2B digital-marketing; narrative content; narrative transportation; B2B purchase risk